Every Child Has a Thinking Style: A Guide to Recognizing and Fostering Each Child's Natural Gifts and Preferences- - to Help Them Learn, Thrive, and Achieve - Lanna Nakone (Berkley Pub. Group, 2006)
Using the latest research into how humans think and learn, this insightful guide gives parents a new way to understand children's thinking styles, sensory preferences, gender, and personality tendencies to help them tailor their child's environment to make it a safe, more learning-friendly place.